Fetal outcome of placenta accreta spectrum disorder patients admitted at Cumilla medical college hospital - Parvin, Jannath; Hossain, Mohammed Kamal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Placenta accreta spectrum disorder (PASD) is a complex obstetric condition associated with significant maternal and fetal morbidity and mortality. Despite its increasing global prevalence, there is limited research focusing on the fetal outcomes of PASD patients, particularly in Asian populations Methods: This observational study was conducted at Cumilla medical college hospital over 18 months, starting from January 2022. A total of 60 patients diagnosed with PASD were included, following specific inclusion and exclusion criteria. Data were collected on sociodemographic characteristics, antenatal care, presenting complaints, and fetal outcomes. Result: The study found that 90% of the participants had live births, while 10% experienced intrauterine death. Among the live births, there was a nearly equal distribution between low and normal birth weights. The sociodemographic distribution was diverse, with the majority of participants falling within the age range of 21-30 years. Half of the participants received regular antenatal care, and antepartum hemorrhage was the most common presenting complaint. Conclusions: The study provides valuable insights into the fetal outcomes of PASD patients, with a notably high rate of live births. The findings also highlight the importance of regular antenatal care and early diagnosis in managing PASD effectively. The study serves as a foundation for future research aimed at improving both maternal and fetal outcomes in PASD.